The Influence of Capital, Digitalization Skills and Financial Management on the Performance of Culinary SMEs in Bojonegoro - Eny Fariyanti; Dimas Tri Laksono; Defi Falentin Febriani; Ika Fatma Maulia; Metha Desy Nursholiha (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the influence of capital, digitalization skills, and financial management on the performance of culinary MSMEs in Bojonegoro Regency. The method used is quantitative. The research sample consisted of culinary MSMEs in Bojonegoro which were taken using random sampling techniques. Data were collected through a Likert scale-based questionnaire and analyzed using multiple linear regression with SPSS software. The results of the study show that capital, digitalization skills, and financial management have a significant positive effect on MSME performance, both partially and simultaneously. Adequate capital provides opportunities for business development, digitalization skills increase competitiveness through efficiency and market reach, while good financial management supports business stability and sustainability. These findings provide practical implications in the form of the need for training, facilitation of access to capital, and increasing financial literacy for MSME actors. This research also provides a basis for local governments to formulate policies that support the development of MSMEs in the digitalization era.